Effect of desvenlafaxine 50 mg and 100 mg on energy and lassitude in patients with major depressive disorder: A pooled analysis. (September 2017) - Lam, Raymond W; Wajsbrot, Dalia B; Meier, Ellen; Pappadopulos, Elizabeth; Mackell, Joan A; Boucher, Matthieu
Nine randomized, double-blind, placebo-controlled studies of major depressive disorder were pooled to evaluate the effects of desvenlafaxine 50- and 100-mg/d on energy and lassitude in adults with major depressive disorder ( n =4279). Changes from baseline to endpoint in 17-item Hamilton Rating Scale for Depression (HAM-D17 ) Work and Activities, Retardation, and Somatic Symptoms General items, HAM-D17 psychomotor retardation factor, and Montgomery-Åsberg Depression Rating Scale Lassitude item were analyzed with a mixed model for repeated measures analysis of variance. Associations between residual energy measures and functional impairment, based on the Sheehan Disability Scale, were modeled using stepwise multiple linear regression. Improvement from baseline was significantly greater for both desvenlafaxine doses versus placebo on all energy symptom outcomes at week 8 (all p ⩽0.005). Both early improvement in HAM-D17 psychomotor retardation at week 2 and residual energy symptoms at week 8 were associated with Sheehan Disability Scale total score at week 8 (all p ⩽0.001). Among Sheehan Disability Scale remitters and responders, the HAM-D17 psychomotor retardation score at week 8 was significantly lower with desvenlafaxine (both doses) than placebo. Desvenlafaxine 50 and 100 mg/d significantly improved energy and lassitude symptoms in patients with major depressive disorder. Both early improvement in energy and fewer residual energy symptoms were associated with functional improvement.